Peran Budaya Masyarakat Terhadap Pembentukan Karakter Siswa Tingkat Dasar - Mochammad Ramdan Samadi; Mohamad Yudiyanto; Laesti Nurishlah (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
Community culture has a very important role in forming the character of elementary level students. This research aims to explore the influence of community culture on the formation of student character in an educational context. The research method used is a literature study which includes in-depth analysis of a number of studies relevant to this topic. Research findings show that community culture has a significant impact on the development of students' character, both through norms, values, traditions and social interactions within the community. Therefore, the character education approach at the elementary level needs to pay attention to and utilize community culture as an important factor in shaping student character.